2020
DOI: 10.1038/s41598-020-72752-7
|View full text |Cite
|
Sign up to set email alerts
|

The comparison of nailfold videocapillaroscopy findings between anti-melanoma differentiation-associated gene 5 antibody and anti-aminoacyl tRNA synthetase antibody in patients with dermatomyositis complicated by interstitial lung disease

Abstract: Dermatomyositis (DM) is frequently complicated by interstitial lung disease (ILD), which increases mortality. This study aims to elucidate the clinical significance of nailfold videocapillaroscopy (NVC) on assessing the disease activity and prognosis of DM-ILD. We compared the NVC findings between anti-melanoma differentiation-associated gene 5 (anti-MDA5) antibody-positive and anti-aminoacyl tRNA synthetase (anti-ARS) antibody-positive patients, the survival and ILD-related death groups, and examined the asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Recent research studies including an AI algorithm-based analysis named “AI score” revealed that lower zone GGO and consolidation demonstrated to be correlated with RP-ILD and were applicable prognostic predictors for MDA5 + DM-ILD ( 31 , 44 ). Besides, the scores of microhemorrhage, capillary disorganization, spontaneous pneumomediastinum, and neoangiogenesis were significantly correlated with known poor prognosis factors of DM-ILD and total fibrosis scores of chest HRCT ( 37 , 45 , 46 ). Some research studies ( 9 , 29 , 37 , 40 , 47 ) have reported that anti-MDA5-positive and non-survivors presented higher serum AST level.…”
Section: Discussionmentioning
confidence: 88%
“…Recent research studies including an AI algorithm-based analysis named “AI score” revealed that lower zone GGO and consolidation demonstrated to be correlated with RP-ILD and were applicable prognostic predictors for MDA5 + DM-ILD ( 31 , 44 ). Besides, the scores of microhemorrhage, capillary disorganization, spontaneous pneumomediastinum, and neoangiogenesis were significantly correlated with known poor prognosis factors of DM-ILD and total fibrosis scores of chest HRCT ( 37 , 45 , 46 ). Some research studies ( 9 , 29 , 37 , 40 , 47 ) have reported that anti-MDA5-positive and non-survivors presented higher serum AST level.…”
Section: Discussionmentioning
confidence: 88%
“…In addition, in a study it was shown that the presence of more microhaemorrhages, capillary disorganization, and abnormal shapes correlated with poor prognosis and higher lung fibrosis in patients with ILD along with DM [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported the presence of enlarged capillaries correlates with the presence of pulmonary involvement ( 15 ). Furthermore, the presence of microhemorrhages have also been correlated with ILD severity in a combined analysis of patients with MDA-5 antibody positive dermatomyositis and anti-synthetase syndrome ( 20 ). Ultimately, only two patients in our cohort had pulmonary involvement and we were likely underpowered to detect a relationship between ILD and NVC.…”
Section: Discussionmentioning
confidence: 99%